The influence of geogenic factors on fossil fauna of waterfleas (Cladocera) at the Jany and Klenica sites (Western Poland) - Rudna, Marta; Twardy, Juliusz (Acta Geographica Lodziensia, 2021)
The article discusses the impact of the relief and geological structure of a large river valley on the quality of material in two cores of organic deposits. The location of both sites was highlighted, the relief of the physicographical mesoregion in which the research was carried out and the geomorphology of the immediate surroundings of the sites were characterised, and geological conditions were discussed in more detail. Sequences of changes in Cladocera subfossil fauna at both sites were presented and the obtained record of their transformations was interpreted. Additionally, the results of analyses of five selected physicochemi-cal parameters of the tested organic compositions were considered, and the obtained data were interpreted. It was concluded that the location of the studied cores in the valleys of large rivers had a significant impact on the quality of material analysed, which ultimately affects the certainty with which environmental changes and increasing human impact can be inferred and the reliability with which they can be reconstructed.